Model Kebijakan Pendidikan Karakter di Madrasah - Supa’at (Jurnal Pendidikan Islam, 2014)
The behavior deviationism in almost our daily activities has caused the realization that“character education” is very important, and the fact that our education system failed to achieve its goals. Therefore, it looks as if there were no solutions – multidimensions crisis. Education must be a solution of a nation to gain the true development and prosperity. To know what really happen in our educational system and practice, it was done the research, in the 29 Islamic Senior High Schools (MA) in Kudus. These research findings show that the concept of character education has substantively the same concept with the system of Islamic school education (madrasah), its difference is only in the referable value. The concept of philosophical character education refers to anthropocentric, and madrasah refers to theocentric (religion). The socio-historic system of the madrasah is really the model of character education or character based on a character that is suitable for the condition in Indonesia.